The structural and optical properties of Poly(Triarylamine) (PTAA) thin films prepared at defferent spin coating method - Miandal, Kellie; Hoh, Hang Tak; Mohamad, Khairul Anuar; Fuei, Pien Chee; Alias, Afishah (American Scientific Publishers, 2017)
Poly (triarylamine) is one of the well-known organic materials and has several advantaged such as stable in ambient and require low-temperature annealing steps. A series of PTAA thin films were deposited at 1000 rpm to 3000 rpm on a glass substrate by spin coating. The structural and optical properties of the organic p-type semiconductor Poly (triarylamine) at the different spin rate were investigated. All the thin films exhibit approximately over 90% transmittance and the estimated band gap in the range of 3.01-3.14eV. The increasing of the spin rate results in the decreasing of the thickness and this relation obeys the power law relation of the form h ∝ ω –3/2 , while the root mean square (RMS) of the films became more uniform as the spin rate increased.